Sex hormone profiles and associated factors among adult tuberculosis patients at Gondar town, northwest Ethiopia: A comparative cross-sectional study - Eshet Gebrie; Habtamu Wondifraw Baynes; Berihun Agegn Mengistie; Temesgen Kassie; Zeleke Kassahun; Abebe Birhanu; Amanuale Zayede; Elias Chane (PLoS ONE, 2026)
Background Tuberculosis, caused by Mycobacterium tuberculosis, is the second leading cause of death from infectious diseases worldwide. Tuberculosis is associated with alterations in sex hormone levels, particularly testosterone, estradiol, and progesterone. However, previous studies have reported conflicting results, with some showing increased or decreased levels in tuberculosis positive patients, while others found no significant differences. This study aims to assess and compare sex hormone profiles among adult tuberculosis-positive patients and tuberculosis-negative individuals and to identify associated factors. Method A comparative cross-sectional study was conducted from June 15 to August 20, 2024, among 300 eligible adult tuberculosis-positive patients and age-matched tuberculosis-negative individuals in five selected health institutions in Gondar town. Participants were recruited using a simple random sampling technique, and sociodemographic, clinical, anthropometric, and behavioral data were collected through a structured questionnaire. Five milliliters of venous blood were used to determine hormone levels using the Beckman Coulter DXI 800 chemistry hormonal analyzer. Hypogonadism was defined by sex-specific hormones and categorized as primary, secondary, and subclinical. The data were analyzed using SPSS version 25.0. Descriptive statistics, independent t-tests, one-way ANOVA, Mann-Whitney U, Kruskal-Wallis H test, and bivariable and multivariable statistical models were used. A p-value < 0.05 with a 95% CI was considered statistically significant. Result Male tuberculosis-positive patients showed significantly higher estradiol, luteinizing hormone, and FSH (p < 0.001), but lower testosterone (p < 0.001). Newly diagnosed tuberculosis-positive patients had significantly lower progesterone levels (p < 0.005). Female tuberculosis-positive patients showed significantly lower testosterone and progesterone but higher follicle-stimulating hormone levels compared to tuberculosis-negative individuals (P < 0.001). Estradiol and luteinizing hormone levels did not differ significantly in female tuberculosis-positive patients. However, newly diagnosed tuberculosis-positive patients had significantly higher median estradiol levels (p < 0.001). The overall prevalence of hypogonadism was 30.3% (95% CI (25.2–35.9%)), sex [AOR = 11.36, 95% CI (3.6, 36.17)] ( p < 0.001), dietary diversity (participants with lower diversity, including those with no dietary diversity [AOR = 8.98, 95% CI (2.37, 33.99)] ( p = 0.001), those with sometimes [AOR = 9.2, 95% CI (2.77, 30.62)] ( p < 0.001) and a usual dietary diversity [AOR = 3.24, (1.04, 10.06) ( p = 0.042), and cortisol [AOR = 4.01, 95% CI (1.7, 9.5)] ( p = 0.002) levels were significant determinants of hypogonadism in tuberculosis patients. Conclusion Male tuberculosis-positive patients showed significantly higher mean estradiol, luteinizing hormone, and follicle-stimulating hormone but lower testosterone levels, while female tuberculosis-positive patients had significantly lower testosterone and progesterone and higher follicle-stimulating hormone levels. There was a higher prevalence of hypogonadism, particularly in males. Early diagnosis of these hormonal changes is crucial in tuberculosis-positive patients to prevent complications such as impaired gonadal function related to hormonal disturbances.